The Federation of Cuban Women and Gender Equality. - KHAN, ZERIN MAHZABIN (Canadian Woman Studies)
The article discusses the Federation of Cuban Women (FMC) and its efforts to promote gender equality in Cuba from 1960 to 1990. The FMC aimed to improve the lives of Cuban women by addressing issues of gender discrimination in the workplace, home, and education. While the FMC's campaigns led to positive changes for women, they also served as a resource for the revolutionary cause. The article highlights the impact of FMC's campaigns on Cuban women and the challenges they faced in achieving gender equality.